Fabrication and characterization of thymol-loaded nanofiber mats as a novel antimould surface material for coating cheese surface - Tatlisu, Nevruz Berna; Yilmaz, Mustafa Tahsin; Arici, Muhammet (ELSEVIER, 2019)
This study covers fabrication and characterization of thymol-loaded nanofiber (TLNs) mats and evaluation of their potential to be used as novel antimould surface coating material for limitation of mould development of Aspergillus parasiticus on kashar cheese surface. Different ratios of polyvinyl alcohol (PVA)/whey protein (WP) were electrospun to yield cylindrical and fine (similar to 370 nm in diameter) polymeric nanofiber mats. The fabricated nanofibers were characterized in terms of their zeta potential, electrical conductivity, molecular, thermal and morphological properties. These results revealed that there were intermolecular interactions between thymol and functional groups of PVA and WP. The most uniform nanofiber structure with smooth beadless appearance could be observed in thymol-free nanofibers (TFNs) fabricated from 60/40 ratio of PVA/WP. The nanofiber diameter and electrical conductivity values were significantly increased by increase in PVA and WP ratios, respectively. The nanofiber mats had dispersion ( - 7.60 mV of zeta potential) and good thermal stability (an endothermic peak at similar to 215 degrees C) properties. In vitro antimould activity tests results showed that TLNs mats could show a higher efficiency against mycelial growth of A. parasiticus than free thymol. In situ test results obtained at the 7th storage day confirmed in vitro test results with respect to visual inspections on coated and uncoated cheese surface, revealing that the coating of kashar cubes with TLNs prevented the growth of A. parasiticus on the coated cheeses. The results of this study shows that TLNs mats can be used an antimould surface material to limit mould growth on coated cheeses during storage period.
Keywords: Antimould surface-coating material; Electrospinning; Nanofiber mats; Thymol; Kashar cheese; AFLATOXIN-PRODUCING STRAINS; WHEY-PROTEIN ISOLATE; ESSENTIAL OIL; ASPERGILLUS-PARASITICUS; CHITOSAN NANOPARTICLES; HEAT-TREATMENT; STABILITY; WORLDWIDE; OREGANO; STARCH; Food Science & Technology